The role of bone modifying agents for secondary osteoporosis prevention and pain control in post-menopausal osteopenic breast cancer patients undergoing adjuvant aromatase inhibitors - Galvano, Antonio; Gristina, Valerio; Scaturro, Dalila; Bazan Russo, Tancredi Didier; Tomasello, Sofia; Vitagliani, Fabio; Carità, Federica; La Mantia, Maria; Fulfaro, Fabio; Bazan, Viviana; Mauro, Giulia Letizia; Russo, Antonio (Frontiers in Endocrinology, 2023)
HT blocks the hormone-mediated growth signal dramatically reducing estrogenic levels with AIs becoming a crucial component of the treatment mainstay in patients with early BC. Postmenopausal BC patients receiving HT present with a significant risk of secondary osteoporosis with AIs ultimately leading to an accelerated rate of bone resorption and thus decreased BMD. This was an observational retrospective clinical study that consecutively enrolled early BC patients with osteopenia to compare the impact of alendronate versus denosumab on secondary osteoporosis prevention and pain control. We identified two groups of patients treated with denosumab 60 mg by subcutaneous injection once every six months or alendronate 70 mg orally once a week. All the patients underwent a baseline physiatric evaluation (T0) and underwent a follow-up visit after 18 months (T1) together with femoral and vertebral Dual-Energy X-ray Absorptiometry (DEXA) exam evaluating T-Score marks. A total of 50 early BC patients were considered eligible and consecutively enrolled in our study. Our results showed that the addition of treatment with alendronate or denosumab led to a significant T-score improvement at the lumbar spine level (-1.92 vs -1.52, p=0.03), with a comparable contribution from alendronate (-1.60 vs -1.45, p=0.07) and denosumab (-2.26 vs -1.58, p=0.07). Regarding the femoral region, neither alendronate (-0.98 vs -1.07, p=0.23) nor denosumab (-1.39 vs -1.34, p=0.81) were able to produce any statistically relevant effect. However, concerning pain control, BMAs had a significant impact on reducing NRS scores in the general population (T1 3.94 vs. baseline 4.32, p=0.007), with a likely specific contribution from alendronate (T1 3.52 vs. baseline 3.88, p=0.004) compared to denosumab (T1 4.36 vs baseline 4.76, p=0.12), without any differences in analgesic therapy assumption over time (p=0.93). Our retrospective findings confirmed that both alendronate and denosumab significantly contributed to preventing secondary osteoporosis in early BC patients with low BMD undergoing AIs, mostly at the lumbar spine level. Moreover, alendronate seemed to significantly impact pain control in such patients further supporting alendronate as a cost-effective option in this frail setting. However, BMAs particularities should be carefully considered on an individual basis according to specific clinical contexts.